EFFECTIVENESS OF PLANT-BASED DIET ON REDUCING THE RISK OF TYPE 2 DIABETES MELLITUS: A LITERATURE REVIEW - Farahdina Amelia Rahmah; Amalia Masithoh; Asri Fatikhatul Husna; Annisa Rahma Fadhila; Nurkhasanah Nurkhasanah; Izka Sofiyya Wahyurin (Media Gizi Indonesia, 2022)
Prevalence of Type 2 Diabetes Mellitus (T2DM) disease in Indonesia is still classified as high. Dietary pattern is a factor that affects the occurrence of T2DM, hence patients' dietary pattern must be monitored to avoid further health complications. One of the interventions that can be applied is a plant-based diet, with a consumption pattern of plant-food such as fruit, vegetable, nut, and seed. The aim of this literature study is to identify the effectiveness of plant-based diet in patients with T2DM. This study was conducted using literature review method that resulted in six relevant journals within the last ten years from Google Scholar, PubMed/Medline, Science Direct, and Wiley Online Library. The results of this study show that a plant-based diet affects weight loss, body mass index, blood glucose (HbA1C, fructosamine, fasting plasma glucose), and hormones (insulin, GLP-1, PYY, PP, amylin). It proves that plant-based diets have a positive impact on people with T2DM patients.